Multiloop and Prediction Based Controller Design for Sugarcane Crushing Mill Process - Sandeep Kumar Sunori; Pradeep Kumar Juneja; Anamika Bhatia Jain (Institute of Advanced Engineering and Science, 2015)
In the present work a sugarcane crushing mill is presented as a MIMO system with high multivariable interaction.A linear model of the plant is taken with flap position and turbine speed as manipulated variables and mill torque and buffer chute height as controlled variables.The multiloop PI controller has been designed for this plant by first investigating the RGA and the value of Niederlinski index of this plant.The decoupling of this system is done and the respective open loop and closed loop step responses are observed and compared with those of the composite MIMO system. Also the performance of multiloop controller is compared with controller designed using model predictive control system strategy for this plant.